Voluntary Running Aids to Maintain High Body Temperature in Rats Bred for High Aerobic Capacity - Karvinen, Sira M.; Silvennoinen, Mika; Ma, Hongqiang; Törmäkangas, Timo; Rantalainen, Timo; Rinnankoski-Tuikka, Rita; Lensu, Sanna; Koch, Lauren G.; Britton, Steven L.; Kainulainen, Heikki (Frontiers in Physiology, 2016)
The production of heat , i.e. thermogenesis, is a significant component of the metabolic rate, which in turn affects weight gain and health. Thermogenesis is linked to physical activity (PA) level. However, it is not known whether intrinsic exercise capacity, aging, and long-term voluntary running affect body temperature. Here we use rat models that differ for maximal running capacity (Low capacity runners, LCR and High capacity Runners, HCR) to study the connection between PA and body temperature. Ten HCR and ten LCR female rats were studied between 9 and 21 months of age. Rectal temperature of HCR and LCR rats was measured before and after one year voluntary running/control intervention to explore the effects of aging and PA. Also, we determined whether injected glucose and spontaneous activity affect the body temperature differently between LCR and HCR rats at 9 vs 21 months of age. HCRs had on average 1.3C higher body temperature than LCRs (p < 0.001). Aging decreased the body temperature level of HCRs to similar levels with LCRs. The opportunity to run voluntarily had a marked impact on the body temperature of HCRs (p < 0.001) allowing them to maintain body temperature at a similar level as when at younger age. Compared to LCRs, HCRs were spontaneously more active, had higher relative gastrocnemius muscle mass and higher UCP2, PGC-1α, cyt c and OXPHOS contents in the skeletal muscle (p < 0.050). These results suggest that higher PA level together with greater relative muscle mass and higher mitochondrial content/function contribute to the accumulation of heat in the HCRs. Interestingly, neither aging nor voluntary training had a significant impact on core body temperature of LCRs. However, glucose injection resulted in a lowering of the body temperature of LCRs (p < 0.050), but not that of HCRs. In conclusion, rats born with high intrinsic aerobic capacity and better health have higher body temperature compared to rats born with low aerobic capacity and disease risk. Voluntary running allowed HCRs to maintain high body temperature during aging, which suggests that high PA level was crucial in maintaining the high body temperature of HCRs.